Plankton diversity and its heavy metal content in Ratai Bay of Pesawaran district, Lampung, Indonesia - Endang Linirin Widiastuti; A. D. Afifa; T. Tugiyono; S. Umar; D. F. Mumtazah; S. Hadi (IWA Publishing, 2023)
Artisanal and small-scale gold mining (ASGM) activity in Way Ratai River produces heavy metal wastes; therefore, further information regarding heavy metal concentrations in the water was needed, especially in plankton samples. Furthermore, the determination of plankton diversity was also carried out in the waters of Way Ratai to determine the bioconcentration factor (BCF). Eight sampling sites were chosen along the river reaching the coast of Way Ratai. The research was conducted in November 2020 and March 2021. Ten heavy metals, Ag, Cd, Co, Cr, Cu, Fe, Mn, Pb, and Zn that are commonly found in mining areas, were determined in the water and plankton samples by using ICP-OES. The results indicated that the highest concentration found was Fe in plankton samples (0.725 mg/L in the river and 1.294 mg/L on the coast). Meanwhile, contents of Cd, Cu, Fe, Mn, and Zn in the river exceeded the predetermined water quality standards, while Ag and Pb metals were not detected. The Cd, Cr, Cu, Pb, and Zn content in seawater also exceeded quality standards. The highest BCF value (12.96) was found for Fe at station G, whereas the lowest BCF value (0.13) was found for Ag at stations G and H. HIGHLIGHTS Plankton and water samples were collected from the river and coastal areas of Way Ratai.; 77 and 36 types of plankton were found in freshwater and coastal water, respectively.; Seven heavy metals, namely Fe, Mn, Zn, Cd, Cu, Cr, and Pb, were found to exceed the quality standard set by the Government Regulation of the Republic of Indonesia and the Regulation of the Minister of the Environment.;